Pengukuran Indeks Daya Saing Industri Kecil Menengah (IKM) di Jawa Tengah - Wiyadi Wiyadi (Jurnal Siasat Bisnis, 2009)
This research aims to analyze the small and medium industries competitiveness in the manufacturing sector in Central Java by using the framework of Porter's diamond model. Measurement of the competitiveness index is using the value established in the industry rankings, the company, dimensions and elements. Based on the results of the index values calculated, small and medium industries in the manufacturing sector in Central Java are highly competitive both for each dimension and overall dimensions. According to the results of independent analysis of samples t test found no significant difference between the competitiveness of small industries with medium industries. Small and medium industries in the manufacturing sector in Central Java has also contributed to the regional economy, especially in absorbing labor, establishment of regional gross domestic product (GDP), providing the output value, non-oil exports, and the absorption of investment value.Keyword: small and medium industries, competitiveness index, manufacturing sector